(3GdgOjI GdfGaYI dTQM efXheI GdhGVMIs - (3YHO GdcQje Hf YeQ GdWQGHdSi GdeOfj GdMfajs; (3HQgGf GdOjf EHQGgje Hf CHj HcQ GdLYHQj,J (B687 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ YHO GdcQje GdWQGHdSi deG cGf GdbQBf GdeLjO CYXe eYLRI ddfHi Udi Gddg Ydjg hSde HeG GMJhi Ydi GdaUGMI hGdHdGZI s
(3BNQgG (B:s
(3hbGd eGdc QVi Gddg JYGdi Yfg JaJQV bQGAI GdaGJMI HLejY MQhagG YdiGdEeGe GdaP Ohf GdeCehe ai cd QcYI hQhi Yfg hai GdfUa hai QcYI hGMOI hQLM GdChdGO s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1996s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs